2017
DOI: 10.7213/psicolargum.v30i69.23284
|View full text |Cite
|
Sign up to set email alerts
|

O uso de álcool por adolescentes: Uma comparação por gênero

Abstract: Objetivo: Examinar a relação existente entre o gênero e o uso de álcool em adolescentes.Método: A amostra foi composta por 1.138 adolescentes, dos quais 58% eram do sexo feminino,com média de idade de 16 anos (DP = 1,45). Para a coleta dos dados foi utilizado um questionário autoaplicável, cujas análises foram feitas por meio de estatística descritiva e teste bivariado, a fim de verificar a existência de associações entre as variáveis. Resultado se discussão: 76% dos adolescentes afirmam ter ingerido bebida al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…Recent studies have also shown the relationship between alcohol consumption and parental supervision 1,3,22,23 , corroborating the findings of this study and highlighting the relevance of the parents' presence and their possible direct relationship with greater discipline and norms, which, consequently, contribute to the development of important social skills for the adoption of protective behaviors to the use of alcohol, such as the choice of friends, recognition of the risks involved, among others 1 . A study that analyzed the causal network of alcohol use also showed that the greater participation of parents contributed to the increase of adolescents' self-esteem, which, in turn, contributed to the lower consumption of alcohol 23 . The present study demonstrated a dose-response relationship of this finding, indicating a potential confirmation of psychosocial mechanisms of the negative effect that the parents' absence on the daily life and activities of adolescents have on alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have also shown the relationship between alcohol consumption and parental supervision 1,3,22,23 , corroborating the findings of this study and highlighting the relevance of the parents' presence and their possible direct relationship with greater discipline and norms, which, consequently, contribute to the development of important social skills for the adoption of protective behaviors to the use of alcohol, such as the choice of friends, recognition of the risks involved, among others 1 . A study that analyzed the causal network of alcohol use also showed that the greater participation of parents contributed to the increase of adolescents' self-esteem, which, in turn, contributed to the lower consumption of alcohol 23 . The present study demonstrated a dose-response relationship of this finding, indicating a potential confirmation of psychosocial mechanisms of the negative effect that the parents' absence on the daily life and activities of adolescents have on alcohol consumption.…”
Section: Discussionsupporting
confidence: 89%
“…Considerando os resultados do questionário sociodemográfico, verificouse entre os escolares o predomínio da religião evangélica, seguida de longe pela católica, em dissonância com a literatura que, majoritariamente, apresenta a religião católica com maior proporção de adeptos. No entanto, estudos apontam que estamos vivendo uma transição religiosa nos últimos anos (Dallo;Martins, 2011;Freitas;Saldanha, 2012;Queiroz et al, 2021).…”
Section: Discussionunclassified
“…Boys are at increased risk of practicing binge drinking compared with girls 9 . This difference can be related to social and cultural norms and historical conditions that built the concepts of man and woman 10 . The discriminatory idea of the role of man frequently presumes that alcohol consumption/binge drinking is an expression of masculinity 11 .…”
Section: Discussionmentioning
confidence: 99%